Anti-bacterial zinc-doped calcium silicate cements: Bone filler. Issue 11 (1st August 2018) - Eltohamy, M.; Kundu, B.; Moon, J.; Lee, H.-Y.; Kim, H.-W.
Abstract: A bone-filler is expected to accomplish diverse purposes such as osteoblastogenesis, osteoclastogenesis and anti-bacterial activity. Taken into consideration of the potent antibacterial activity of certain trace elements, in present study, the effect of Zn-doping in tricalcium silicate cement is explored by means of its biological function. Cement setting reaction is slowed down with Zn addition, while the compressive strength of the doped cement increases. In stimulating body fluid, Zn is incorporated slowly into developing apatite nuclei; it results in restricted apatite crystallization and formation of amorphous apatite layer. The slow release of zinc ions into culture medium, greatly enhances the proliferation and alkaline phosphatase activity of rat bone marrow stromal cells. Released Zn 2+ also takes part in bone-remodeling; facilitates osteoclastogenesis in RAW 264.7 (in presence of RANKL). Furthermore, the accumulation of Zn 2+ at bacterial membrane impairs membrane permeability, causing death of both Gram-positive ( Staphylococcus aureus ) and Gram-negative ( Escherichia coli ) bacterias. The data indicate a gradual release of Zn ions from the bioactive injectable doped calcium silicate; these ions modulate bone metabolism induce concentration-dependent cell proliferation, render osteo-inductivity to self-curing cement. Zn also imparts anti-bacterial property to C3 S; perquisite for medical bone implants. Graphical abstract: fx1